Difficulties in modelling ARDS (2017 Grover Conference Series) - Stefan Uhlig; Wolfgang M. Kuebler (Pulmonary Circulation, 2018)
Fifty years after the first description of acute respiratory distress syndrome (ARDS), none of the many positive drug studies in animal models have been confirmed in clinical trials and translated into clinical practice. This bleak outcome of so many animal experiments shows how difficult it is to model ARDS. Lungs from patients are characterized by hyperinflammation, permeability edema, and hypoxemia; accordingly, this is what most models aim to reproduce. However, in animal models it is very easy to cause inflammation in the lungs, but difficult to cause hypoxemia. Often – and not unlike in patients – models with hypoxemia are accompanied by cardiovascular failure that necessitates fluid support and ventilation, raising the question as to the role of intensive care measures in models of ARDS. In our opinion, there are two major arguments in favor of modelling intensive care medicine in models of ARDS: (1) preventing death from shock; and (2) modelling ventilation and other ICU measures as a second hit. The preferable predictive endpoints in any model of ARDS remain unclear. At present, the best recommendation is to use endpoints that can be compared across studies (i.e. PaO 2 /FiO 2 ratio, compliance, wet-to-dry weight ratio) rather than percentage data. Another important and often overlooked issue is the fact that the thermoneutral environmental temperatures for mice and rats are 30℃ and 28℃, respectively; thus, at room temperature (20–22℃) they suffer from cold stress with the associated significant metabolic changes. While, by definition, any model is an abstraction, we suggest that clinically relevant models of ARDS will have to closer recapitulate important properties of the disease while taking into account species-specific confounders.